A questionnaire survey of stress and bullying in doctors undertaking research. Issue 940 (17th February 2004) - Stebbing, J; Mandalia, S; Portsmouth, S; Leonard, P; Crane, J; Bower, M; Earl, H; Quine, L
Abstract : Background: Research is an increasingly important aspect of higher medical training for many doctors. Studies investigating sources of stress, isolation, and workplace bullying have not previously sought information in this setting. Methods: An internet based questionnaire survey of doctors undertaking research (n = 259) was conducted to examine stressors and levels of job satisfaction in this potentially vulnerable group. In order to assess overall levels of satisfaction, we asked whether doctors would recommend their research post to a colleague. Results: There was a statistically significant association between those who would not recommend their post to a colleague and those who had difficulties in arranging funding and in writing up (p<0.001). Further significant correlations were found between dissatisfaction with the post and lack of help, support, and advice from supervisors and colleagues, wanting to change supervisors, experience of the major categories of workplace bullying, and having an inadequate clinical commitment (p<0.001). When the significant variables were entered into a multivariate analysis, the results showed that dissatisfaction was associated with wanting to change supervisors and with a threat to professional status. Conclusions: Stress and bullying are common in doctors undertaking research. These findings have important implications for medical training and for doctors choosing research projects. Setting up systems of support may have important benefits.